2020
DOI: 10.1017/s1047951120000578
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative Brugada electrocardiographic pattern, polymorphic ventricular tachycardia, and sudden death in a child after administration of propofol anaesthesia

Abstract: A 9-year-old African-American girl presented with sudden cardiac arrest a few hours after adenotonsillectomy. She received anaesthesia which included propofol during the procedure. Her electrocardiogram (EKG) showed type 1 Brugada pattern, and genetic testing revealed a variant of unknown significance in desmoplakin (DSP) gene. We discuss the association between propofol, Brugada EKG pattern, and malignant ventricular arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…8 We are in agreement with the authors that altered autonomic tone in the post-operative period could have contributed to the observed electrocardiographic findings and Brugadarelated malignant arrhythmias in this patient and have stated so in our report. 1 We are also cognizant of the fact that it is difficult to ascribe causality based on a single patient report; however, we do believe that reports like ours inform the need for systematic evaluation of cardiac electrical effects of anesthetics such as propofol in the young.…”
Section: Utkarsh Kohlimentioning
confidence: 65%
See 1 more Smart Citation
“…8 We are in agreement with the authors that altered autonomic tone in the post-operative period could have contributed to the observed electrocardiographic findings and Brugadarelated malignant arrhythmias in this patient and have stated so in our report. 1 We are also cognizant of the fact that it is difficult to ascribe causality based on a single patient report; however, we do believe that reports like ours inform the need for systematic evaluation of cardiac electrical effects of anesthetics such as propofol in the young.…”
Section: Utkarsh Kohlimentioning
confidence: 65%
“…A limited echocardiogram was performed in the emergency department during atrial rhythm and showed normal biventricular size, low normal biventricular function, and no evidence of pericardial effusion. 1 We also measured plasma troponin concentration at presentation which was only mildly elevated (0.06 ng/mL; normal < 0.03 ng/mL). The echocardiographic finding of low normal biventricular function which is common after cardiopulmonary arrest and only mild elevation in serum troponin concentration noted in this patient argue against severe myocardial damage from prolonged severe hypoxemia and ischemia.…”
Section: Utkarsh Kohlimentioning
confidence: 99%
“…( 51) It has been listed as a Class IIa drug for Brugada syndrome (12). In the studies we reviewed we found that there were instances where patients suffered cardiac arrest (28,38,40,41,43) or ventricular fibrillation (24,(34)(35)(36)(37)(38)44) after propofol administration. In some patients it also showed conflicting ECG changes with some studies showing ST elevation (59) in a few patients while other showing ST depression (55).…”
Section: Propofolmentioning
confidence: 99%
“…We read with great interest the article with the title "Post-operative Brugada electrocardiographic pattern, polymorphic ventricular tachycardia, and sudden death in a child after administration of propofol anaesthesia". 1 They alluded that a fatal ventricular arrhythmia was induced by propofol in a patient with Brugada syndrome. Imputability analysis can be done using different methods, including expert judgement, the World Health Organisation, or another algorithmic method.…”
Section: Dear Editormentioning
confidence: 99%